Knowledge and Attitudes of Dental Students in Prescribing Antibiotics for Pediatric Dental Patients in Bhubaneswar City, Odisha: A Cross-Sectional Study - Ankita Sinha1 , Susant Mohanty2 , Sonu Acharya3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Antibiotics are the most widely prescribed therapeutic agents in dentistry, hence it representsan important aspect of dental practice. The inept use of antibiotics for the treatment of dental infections inchildren is a leading cause of developing microbial resistance.Objective: The objective of this study is to investigate the knowledge & attitudes of a group of dentalstudents when prescribing antibiotics during the treatment of pediatric dental patients.Method: This is a questionnaire-based cross-sectional study conducted in a group of 300 dental studentsfrom various dental colleges of Bhubaneswar city, Odisha. The questionnaire consisted of closeended questions, structured under three main headings. Data collected were analyzed using SPSS statisticsversion 24.Results: The prime findings were that amoxicillin is the most commonly prescribed antibiotic, most studentshad not received training on antibiotic prescribing and had treated more than 10 child patients per week &their concordance with guidelines on antibiotic prescribing was generally low.Conclusion: This cross-sectional study shows there is a need to improve the knowledge on antibioticprescribing for children.